KAJIAN PRODUKSI BIOINSEKTISIDA DARI Bacillus thuringiensis subsp israelensis PADA MEDIA TAPIOKA - Abdul Aziz Darwis, Khaswar Syamsu dan Ummi Salamah (Department of Agroindustrial Technology, Bogor Agricultural University, 2004)
ABSTRACTBacillus thuringiensis subsp israelensis (B.t.i) as one of the Bacillus thuringiensis (B.t) species produces crystal protein called delta endotoxin. As other B.t crystal protein, this crystal is specifically toxic to mosquitoes and blackflies. This research of B.t.i fermentation used tapioca as carbon source and urea as nitrogen source. The composition of media fermentation used were 0.5%, 1.0%, 1.5%, 2.0%, 2.5% and 3.0% of tapioca, and 1% urea. The result shows that B.t.i was able to grow in all treatment units. Bioassay shows that the best performance was obtained from media with 2.0% tapioca.Key words: Bacillus thuringiensis, tapioca